Development of Simulation Scenario for the Circulatory System in Humans Material for Grade XI High School - Saputri, Winda Eka; Hamka L, Hamka L; Rachmawaty, Rachmawaty (Universitas Negeri Makassar, 2023)
This research aims to produce simulation scenarios for biology materials in Grade XI of Senior High School focusing on the mechanism of human blood circulation. The type of research used is R&D research employing the 4D development model (Define, Design, Develop, and Disseminate). The validity and simulation scenarios were assessed by two validated biologist experts from the Faculty of Mathematics and Natural Sciences (FMIPA) at UNM, using simulators and simulation scenario questionnaires. Based on the questionnaire data obtained, the validity of the simulation scenario is Va = 4.12, which falls into the